2001
DOI: 10.1039/b103647p
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses, structures, magnetic, and spectroscopic properties of cobalt(ii), nickel(ii) and zinc(ii) complexes containing 2-(6-methyl)pyridyl-substituted nitronyl and imino nitroxide†

Abstract: Chelate complexation of 4,4,5,5-tetramethyl-2-(6-methyl-2-pyridyl)imidazolin-1-oxyl 3-oxide (NITmepy) and 4,4,5,5-tetramethyl-2-(6-methyl-2-pyridyl)imidazolin-1-oxyl (IMmepy) to cobalt() chloride (bromide) or zinc() chloride afforded tetrahedral four-co-ordinate (T -4) complexes, [MX 2 (NITmepy)] and [MX 2 (IMmepy)] (MX = CoCl (1 and 2), CoBr (1Br and 2Br) or ZnCl (3 and 4), respectively) containing either a six-or a five-membered chelate ring as determined by single-crystal X-ray analysis. The formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 21 publications
3
17
0
Order By: Relevance
“…The C-O bond distance is elongated to 1.258(3) Å and the ligand bite angle is 102.11(7)°, the largest of any of the complexes, consistent with the tetrahedral geometry. The Co-O, CoN, and Co-Cl bond distances in 10 (1.963(2) Å, 2.044(2) Å, 2.340(7) Å and 2.2500(7) Å, respectively) are comparable to those reported for the tetrahedral complex [CoCl 2 (NITMepy)] [41].…”
Section: Synthesis and Characterizationsupporting
confidence: 71%
“…The C-O bond distance is elongated to 1.258(3) Å and the ligand bite angle is 102.11(7)°, the largest of any of the complexes, consistent with the tetrahedral geometry. The Co-O, CoN, and Co-Cl bond distances in 10 (1.963(2) Å, 2.044(2) Å, 2.340(7) Å and 2.2500(7) Å, respectively) are comparable to those reported for the tetrahedral complex [CoCl 2 (NITMepy)] [41].…”
Section: Synthesis and Characterizationsupporting
confidence: 71%
“…Several studies have shown that antiferro-or ferromagnetic interactions were operative through the central metal ions, such as Ti(IV), Cu(I), Ag(I), Hg(II), Zn(II) and Cd(II) [24][25][26][27][28][29][30][31][32][33][34][35][36][37]. In these complexes, the metal ions play an active role in aiding the exchange coupling between the radicals.…”
Section: Introductionmentioning
confidence: 98%
“…By using this approach, various highly interesting species such as molecular-based ferromagnets [5][6][7], single-chain magnets (SCMs) [8][9][10][11][12][13], single-molecule magnets (SMMs) [14][15][16][17][18][19] and molecule spin transition species [20][21][22][23] have been achieved so far. However, most of the work performed in this area has involved in copper(II), nickel(II), manganese(II) or lanthanide compounds, and the reported cobalt(II)-radical compounds are currently very scarce [24][25][26]. It is well known that the high-spin cobalt(II) atom may exhibit large magnetic anisotropy due to strong spin-orbital coupling.…”
Section: Introductionmentioning
confidence: 98%